The Monetary Approach to the Balance of Payments : A Collection of Research Papers by Members of the Staff of the International Monetary Fund. (International Monetary Fund, 1977)
This volume brings together several of the most important research papers on the monetary approach to the balance of payments prepared by IMF staff members. The 11 papers record, the contribution made by the IMF's staff to the development of the monetary approach, which is now widely accepted by academic economists and policymakers alike.